Olive oil consumption and risk of cardiovascular disease and all-cause mortality: A meta-analysis of prospective cohort studies - Xia, Meng; Zhong, Yi; Peng, Yongquan; Qian, Cheng (Frontiers in Nutrition, 2022)
Background: Epidemiological studies have shown the preventive effects of olive oil consumption against cardiovascular events and all-cause deaths, but the results remain inconsistent. Herein, we performed a meta-analysis to elucidate this association. Methods: A systematical literature search was conducted in online databases (PubMed and Scopus) through July 31, 2022. Prospective cohort studies providing the risk of total CVD or all-cause mortality for olive oil consumption were included. Relative risks (RRs) and 95% confidence intervals (CIs) were aggregated using random-effect model. Results: This meta-analysis included 13 studies comprising a total of 13 prospective cohorts. Compared with lower consumption, higher consumption of olive oil conferred a significantly reduced risk in CVD (RR: 0.85, 95% CI: 0.77–0.93, p<0.001) and all-cause mortality (RR: 0.83, 95% CI: 0.77–0.90, p<0.001). This beneficial effect was not modified by the potential confounders such as study country, sample size, follow-up duration, gender, and type of olive oil consumed. In dose-response meta-analysis, the summary RR of per 5-g/d increase in olive oil intake was 0.96 (95% CI: 0.93–0.99, p=0.005) for CVD and 0.96 (95% CI: 0.95–0.96, p<0.001) for all-cause mortality. Nonlinear associations of olive oil intake with CVD and all-cause mortality were also identified (both p for nonlinearity <0.001), with little additional or no risk reduction observed beyond the consumption of approximately 20 g/d. Conclusion: Olive oil consumption is inversely related to the risk of CVD and all-cause mortality. Such benefits seem to be obtained with an intake of olive oil up to 20 g/d, which deserves further exploration in future studies.